Development Programme 2002-2003 Government of Gujarat - Planning Commission (Planning Commission, 2002)
Gross State Domestic Product (GSDP) at factor cost at constant (1993-94) prices in 2000- 01 has been estimated at Rs. 76657 crore as against Rs. 74984 crore in 1999-00 registering a growth of 2.2 percent during the year. At current prices, GSDP at factor cost in 2000-01 has been estimated at Rs. 112049 crore as against Rs. 106427 crore in 1999-00 showing an increase of 5.3 percent during the year.
Government of Gujarat, General Administration Department Planning Division